Effect of temperature on N2O emissions from a highly enriched nitrifying granular sludge performing partial nitritation of a low-strength wastewater. (October 2017) - Reino, Clara; van Loosdrecht, Mark C.M.; Carrera, Julián; Pérez, Julio
Abstract: In the race to achieve a sustainable urban wastewater treatment plant, not only the energy requirements have to be considered but also the environmental impact of the facility. Thus, nitrous oxide (N2 O) emissions are a key-factor to pay attention to, since they can dominate the total greenhouse gases emissions from biological wastewater treatment. In this study, N2 O production factors were calculated during the operation of a granular sludge airlift reactor performing partial nitritation treating a low-strength synthetic influent, and furthermore, the effect of temperature on N2 O production was assessed. Average gas emission relative to conversion of ammonium was 1.5 ± 0.3% and 3.7 ± 0.5% while the effluent contained 0.5 ± 0.1% and 0.7 ± 0.1% (% N-oxidized) at 10 and 20 °C, respectively. Hence, temperature increase resulted in higher N2 O production. The reasons why high temperature favoured N2 O production remained unclear, but different theoretical hypotheses were suggested. Graphical abstract: Highlights: The partial nitritation process at mainstream conditions produced low N2 O emissions. A temperature effect was shown on N2 O gas emissions in a partial nitritation process. Temperatures higher than 15 °C increased N2 O emissions in the partial nitritation.